Analysis of Leadership and Work Environment Employee Performance Through Job Satisfaction as an Intervening (Case Study at the Tirta Kampar Drinking Water Company Company) - Suarni Norawati; Afdira Afdira; Zamhir Basem (Komunitas Dosen Indonesia, 2023)
Regional Drinking Water Company Owned Business Entity which provides clean Water Company for the public of Kampar Regency. Providing services to the community requires maximum employee performance so that community satisfaction is achieved. This study aims to identify and analyze the direct influence of leadership and the work environment on employee performance, to identify and analyze the indirect influence of leadership and the work environment on employee performance through job satisfaction, and to identify and analyze the influence of satisfaction on employee performance. The sample study are all employees of the Regional Drinking Water Company Company of Kampar Regency, totaling 76 people. The analysis method using the SEM obtained through the Smart PLS. The findings are: 1) there is no significant direct influence of leadership variables on employee performance. 2) The work environment has a direct and significant effect on employee performance. 3) Leadership is proven to have a significant indirect effect on employee performance through job satisfaction. 4) The work environment is proven to have a significant indirect influence on employee performance through job satisfaction. 5) Job satisfaction has a significant effect on employee performance.